Dinamika Kehidupan Kethoprak di Kabupaten Pati 1950-2007 - Azmi Globalian Nazal; Dhanang Respati Puguh (Jurnal Sejarah Citra Lekha, 2022)
Kethoprak is a traditional performing art originating from Surakarta. Kethoprak is not able to develop optimally in its ownregion, because it cannot compete with wayang wong. The existence of wayang wong in Surakarta is more demanded by the public compared to kethoprak. This situation forced kethoprak groups move to Yogyakarta which is very developed region. Kethoprak is not only performing around Yogyakarta, but also outside the region. Pati Regency is one of the regions which is affected by the development of kethoprak from Yogyakarta. This study discusses the dynamics of kethoprak groups in Pati by applying historical methods. In 1950, kethoprak entered Pati for the first time, especially in Bakaran Village. In the past, kethoprak which come from Yogyakarta, was invited to entertain the people of Bakaran. From its performances, the ideas were emerged from a group of people to form a kethoprak group. In its development, the groups emerged in Pati. The ups and downs colored by the journey of kethoprak in Pati. Kethoprak was once used as a source of income because of the intense performance. Then, with the emergence of modern performance, the existence of kethoprak is increasingly shifted. However, kethoprak in Pati is still able to maintain its existence to survive in the midst of society.